Upah Khataman Al-Qur’an Di Kuburan Perspektikf Ulama Di Kota Sampit Provinsi Kalimantan Tengah - Lukman Hakim; Achmad Junaidi (Syntax Idea)
This research is motivated by the phenomenon of bargaining over wages in the process of completing the Qur'an, which raises various interpretations regarding the legality of such wage bargaining. Based on this, the aim of this research is to understand the views of scholars in Sampit City regarding the practice of bargaining wages for completing the Qur'an. This research is empirical law with a sociological law type, and the approach is socio-legal. The subjects in this study consist of the organizers of Qur'an completions, users of completion services, and scholars in Sampit City. The results of this study show that the views of scholars on the practice of paying for completing the Qur'an at gravesites are divided into two groups, namely, allowing and not allowing. For scholars who allow it, they have various considerations, including mutual assistance, not burdening others, and as compensation for the activities performed by the organizers of the completion who must leave their daily jobs to carry out this completion activity. Whereas for scholars who do not allow it, they adhere to the principle of caution regarding future consequences based on the principle of Saddudz Dzari'ah. Saddudz Dzari'ah ((Ø³ÙŽØ¯Ù‘ÙØ§Ù„Ø°Ù‘ÙŽØ±ÙÙŠØ¹ÙŽØ© is related to the preference of reading the Qur'an at gravesites, burdening the family of the deceased, the commercialization of worship, and the loss of sincerity in reading the Qur'an due to the presence of wages.